Žodžių tvarka ir baltų kalbų sakinio tipo rekonstrukcija - Ambrazas, Vytautas (Baltistica, 1982)
Word order and reconstruction of Baltic sentence type The article deals with mutual relations between word order patterns in Lithuanian and Lettish and points out their importance for the reconstruction of earlier Baltic sentence structure. Statistic evidence reveals the greater frequency of the OV pattern (from 51% to 75%) in dialects and folklore, especially in the older recordings, in comparison with standard language. The ancient character of this pattern is corroborated by the order of components in nominal compounds such as Lith. kraugerỹs “blood-sucker”, varkalỹs (Lett. varkalis) “copper-smith”, bìtkopis (Lett, biškuopis) “honey-taker”. The (S)OV order of the major sentence constituents is in accordance with the majority of phrase constituent patterns in which the modifier (operator) precedes the modified (operandum): AdjNom, PronNom, NumNom, GenNom; AdvV, Adv’Adv, etc. Other patterns with the preceding modifier can be reconstructed for the earlier history of the Baltic languages. The ancient use of postpositions reflect the locatives with -pi< *pie, *en, -na (Lith. Namóp(i), laukè, laukúosna), adverbs Lith. kodė̃l, todė̃l, kodrin, todrin, Lett, kāpēc tāpēc etc. The standard of comparison precedes adjective in the majority of gnomic expressions, proverbs and riddles of Lithuanian folklore and especially in such periphrastic comparatives as Lith. visų̃ geràsis (geriáusias), Lett. vislabâks “best of all”. Nominal phrases with definite adjectives, f. i. Lith. gerasis (<*geras+jis) tėvas, represent ancient determinative constructions preceding nouns while the use of -gu in Old Lithuanian shows the postposition of interrogative particles (even after negative particles, cf. Lith. negu “as”). The historical survey of word order patterns reveals the ancient ambivalence between (S)OV and (S)VO types in Baltic with the prevalence of constructions representing the (S)OV type. In this connection the Baltic languages give evidence of an earlier state of development in comparison with Slavic and manifest a great similarity to Homeric Greek and early Latin. The tendency to fix the position of some modifiers after the modifieds in the history of Baltic languages influenced the prepositional constructions earlier and more consistently than it did the standard of comparison (AdjSt) and major sentence constituents (V, O). The syntactic structure of languages with an ambivalent word order is supposed to be depending not only on the order of the most variable sentence constituents (S, 0, V) but mainly on the complex of more fixed patterns reflected in the distribution of stressed and unstressed positions in the sentence.